Unlocking the cassava treasure: a path to elevate export revenues in Tanzania - Laizer, L.; Kapinga, R.; Maregeri, B.; Ndyetabura, I.; Mtunda, K.; Kessy, R.; Kasubiri, F.; Reuben, F.; Laurent, F. (2024)
Over the past 15 years, Tanzania has implemented the Agricultural Marketing Policy (2008), which provides legal and regulatory guidance to the government and private sector actors in enhancing the quality standards and competitive prices of agricultural commodities. Nevertheless, there exists a gap in understanding how this policy guideline is implemented by market actors at the local level. These knowledge gaps underscore the necessity for a rapid market survey carried out in July 2023, with dried cassava chips used as a case study on agricultural commodities exported to neighbouring countries. The results showed that the average export of dried cassava chips was 209,778 tons in 2020-2022, and the average annual value of exports is estimated at TZS 144.84 billion. However, this market study suggests that market actors possess a low level of awareness regarding quality protocols, and in most locations, the marketing of dried cassava chips is informal and uncoordinated, which affects revenue streams for stakeholders. Additionally, there is limited capacity at most of the border posts, primarily attributed to limited modern operational equipment and technologies. In conclusion, this policy brief calls for the following interventions, which have the potential to enhance competitiveness and promote sustainability within the value chain, thereby generating more revenue for stakeholders: 1. the review of quality standards for local adaptation and implementation; 2. the strengthening of farmer organizations to meet business opportunities; and 3. the investment in infrastructure and technology at border posts.